Agriculture, natural resources, and rural development sector assessment, strategy, and road map Lao People Democratic Republic. (Metro Manila, Philippines Asian Development Bank, 2018)
This report assesses the agriculture, natural resources, and rural development sector in the Lao People Democratic Republic.It provides an overview of challenges and opportunities in the sector as well as priorities for future ADB and government support. It notes that agriculture in the Lao PDR has significant growth potential, and that improving its productivity and promoting commercialization will create jobs for the poor, women, and ethnic minority groups in rural areas. Priorities also include sustainable natural resource management and climate resilience. The conservation and improvement of watersheds will be essential for sustainable irrigation and agricultural production.
Keywords: Agriculture -- Laos; Natural resources -- Economic aspects -- Laos; Electronic books